ENGLISH LANGUAGE PROFICIENCY AMONG TECHNICAL STUDENTS OF KOLEJ KEMAHIRAN TINGGI MARA - MD YUSOF, FARISA JAZIMA; ABU BAKAR, NURUL ASHIKIN; BILAH, SYAMAIZAR (Human Sustainability Procedia, 2018)
Proficiency exclusively in English is one of the main features important for graduates. It serves to support the required skills intechnically based industries. Technical skills alone are not sufficient as the incompetency to communicate in English may cause graduates failure to market themselves internationally. Therefore, this present study aimed to investigate English language proficiency level based on perceptions among technical students of Kolej Kemahiran Tinggi MARA. Three factors; environmental, personal and behavioral factors served as a framework that contributes towards respondents English language proficiency. 279respondents from three selected KKTM were involved to complete the questionnaires provided by the researcher. This is a quantitative research and data was collected and analyzed using Winsteps 3.69.11 based on Rasch Measurement Model Approach and Statistical Packages for Social Science (SPSS) Ver. 20 software.As a result, the findings indicate highest percentages of respondents perceived they have low English proficiency level. It was also found out that the most dominant factors towards English proficiency level among KKTM students was personal factors. The main implications of the research is that there is a need for language educators in KKTM to adjust students’ perceptions and manipulate personal factors such as interest and motivation in their instructional method to produce better graduates competent in English language.